Nanoporous Au: An experimental study on the porosity of dealloyed AuAg leafs. (December 2016) - Grillo, R.; Torrisi, V.; Ruffino, F.
Abstract: We present a study on the fraction of porosity for dealloyed nanoporous Au leafs. Nanoporous Au is attracting great scientific interest due to its peculiar plasmonic properties and the high exposed surface (∼10 m 2 /g). As examples, it was used in prototypes of chemical and biological devices. However, the maximization of the devices sensitivity is subjected to the maximization of the exposed surface by the nanoporous Au, i. e. maximization of the porosity fraction. So, we report on the analyses of the porosity fraction in nanoporous Au leafs as a function of the fabrication process parameters. We dealloyed 60 μm-thick Au23 Ag77  at.% leafs and we show that: a) for dealloying time till to 6 h, only a 450 nm-thick surface layer of the leafs assumes a nanoporous structure with a porosity fraction of 32%. For a dealloying time of 20 h the leafs result fragmented in small black pieces with a porosity fraction increased to 60%. b) After 600 °C-30 minutes annealing of the previous samples, the nanopores disappear due to the Au/residual Ag inter-diffusion. c) After a second dealloying process on the previously annealed samples, the surface nanoporous structure is, again, obtained with the porosity fraction increased to 50%. Graphical abstract: Highlights: Nanoporous Au is produced by dealloying Au23 Ag77 leafs. The porosity is observed to be confined on the leafs surfaces. The porosity fraction evolution is analyzed versus dealloying time. A recovery process of the leafs is observed after thermal processes. Higher porosity fraction are observed after dealloying the recovered leafs.